Chronic alcohol metabolism results in DNA repair infidelity and cell cycle‐induced senescence in neurons. Issue 2 (23rd January 2023) - Sun, Jacquelyne Ka‐Li; Wu, Deng; Wong, Genper Chi‐Ngai; Lau, Tsun‐Ming; Yang, Meigui; Hart, Ronald P.; Kwan, Kin‐Ming; Chan, Ho Yin Edwin; Chow, Hei‐Man
Abstract: Chronic binge‐like drinking is a risk factor for age‐related dementia, however, the lasting and irreversible effect of alcohol on the brain remains elusive. Transcriptomic changes in brain cortices revealed pro‐ageing hallmarks upon chronic ethanol exposure and these changes predominantly occur in neurons. The changes are attributed to a prioritized ethyl alcohol oxidation in these cells via the NADPH‐dependent cytochrome pathway. This hijacks the folate metabolism of the 1‐carbon network which supports the pathway choice of DNA repair via the non‐cell cycle‐dependent mismatch repair networks. The lost‐in‐function of such results in the de‐inactivation of the less preferred cell cycle‐dependent homologous recombination (HR) repair, forcing these post‐mitotic cells to re‐engage in a cell cycle‐like process. However, mature neurons are post‐mitotic. Therefore, instead of successfully completing a full round of cell cycle which is necessary for the completion of HR‐mediated repair; these cells are arrested at checkpoints. The resulting persistence of repair intermediates induces and promotes the nuclear accumulation of p21 and cyclin B—a trigger for permanent cell cycle exits and irreversible senescence response. Supplementation of bioactive 5‐methyl tetrahydrofolate simultaneously at times with ethyl alcohol exposure supports the fidelity of the 1‐carbon network and hence the activity of the mismatch repair. This prevents aberrant and irreversible cell cycle re‐entry and senescence events of neurons. Together, our findings offer a direct connection between binge‐drinking behaviour and its irreversible impact on the brain, which makes it a potential risk factor for dementia. Abstract : Metabolism of ethyl alcohol in neurons via the NADPH‐dependent CYP2E1 axis contributes to heightened risks of dementia in chronic binge‐like drinking. The findings bridged how the consequential cellular metabolic rewiring cross‐talks to the choice of DNA repair and illustrated how unfavourable deployment of a cell cycle‐based DNA repair network aberrantly leads to neuronal senescence. A metabolic‐correction strategy targeting related metabolic changes offers new perspectives in therapeutic design.